Current developments in personalized treatment strategies for elderly acute myelogenous leukemia patients - Xueting Hou; Jizhang Bao (Guoji laonian yixue zazhi)
Acute myelogenous leukemia(AML) is a life-threatening hematologic malignancy that predominantly affects the elderly.Currently, chemotherapy and hematopoietic stem cell transplantation are the primary treatment modalities for AML, though their clinical application is limited in older patients.Recent years have seen the development of novel molecular targeted therapies, such as isocitrate dehydrogenase 1/2 (IDH1/2) and Feline macrophage stimulator-like tyrosine kinase 3 (FLT3) inhibitors, as well as individualized approaches like chimeric antigen receptor T-cell (CAR-T) therapy.However, due to patient heterogeneity and drug resistance, treatment outcomes for elderly AML remain unsatisfactory, underscoring the need for more precise and safer individualized treatment strategies.The combination of chemotherapy with novel targeted or immunotherapies shows promise as a future treatment direction.This research reviews the latest advances in the treatment of elderly AML, with a focus on achieving more individualized and safer therapeutic approaches.